Mercado Turístico y Comportamiento del Consumidor en las Actividades de Ocio y Recreación de la Ciudad de Riobamba, Provincia de Chimborazo - Cortez Valencia, Jamela Sugey (2019)
This research intended to establish the relation between the independent variable “tourist market” and the dependent variable “consumer behavior” in the leisure and recreational activities from Riobamba city, Chimborazo province, to develop this work one took two samples were taken, which were used to obtain the information, first it was of three hundred twenty-two national tourists and the second of fifteen tourist service providers. The type of research correspond to a field, descriptive, correlational-causal process, and the transversal method was applied. Therefore, from this study we can conclude that if exists a positive influence between the tourist market and consumer behavior, which was confirmed in the general hypothesis. With all the results that the research reflected, the need arose to make a portfolio of cultural tourism products.